การวิเคราะห์อภิมานงานวิจัยปัจจัยที่เกี่ยวข้องกับความพึงพอใจในงานของพยาบาล - ปิยะฉัตร ฉ่ำชื่น (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
The purposes of this meta - analysis study were to 1) study research characteristics of factors related to nurses job satisfaction. 2) Identify the factors that influence nurses job satisfaction. 3) compare mean correlation coefficients across research characteristics. 4) account variance of correlation coefficients by research characteristic variables. The 88 studies of cause and effect relationships in Thailand employed during 1976 - 2003 were recruited. Data collected were study moderators including general, substantive, methodological characteristics and research quality. The 663 correlation coefficients of studies were analyzed by using meta -analysis method of Glass, et al. (1987). Those correlation coefficients were divided into 2 groups : antecedent variables (519 correlation coefficients) and consequence variables (144 correlation coefficients). Statistics used in this study were t-test, F-test and Hierarchical stepwise regression analysis. The major findings were as follows: 1. The research characteristics consisted of 3 components including general, substantive and methodological characteristics. 2. The antecedent variables of nurses job satisfaction were managerial factors (r = .504), working factors (r = .148) and personal factors (r = .129) respectively. The six catagories of consequence variables divided into 2 groups : positively correlated with nurses job satisfaction including commitment/ citizenship behavior (r = .408), retention (r = .383) and performance (r = .350), and negatively correlated with nurses job satisfaction including turnover (r = -.311), burn out (r = -.250) and intend to further study (r = -.063). 3. Most of research characteristic variables were statistically significant affected on the mean correlation coefficients of both antecedent and consequence variables of nurses job satisfaction, at .05 level. 4. The research characteristic variables were significantly predicted correlation coefficients of antecedent variables and consequence variables with variance accountedof 57.3 % and 78.9 % respectively.